GENERAL AND SPECIFIC REQUIREMENTS FOR THE TEACHING STAFF OF THE DEPARTMENT OF PHYSICAL CULTURE UNIVERSITIES RUSSIAN INTERIOR MINISTRY - Aleksander Kudrya; Pavel Koshelev; Alexander Zemlyanoy (Вестник Северо-Кавказского федерального университета)
The article discusses the activities of employees - experts ofphysical training and sports characterizing the one hand, a wide range of duties and the need to work with all members of the Interior, and with another -lack of subordinates at work.